Can a Good Mediator also be a Good Arbitrator? - Moens, Gabriël (LexisNexis Hong Kong, 2009)
This Article considers whether a good mediator can also be a good arbitrator. It provides examples of domestic legislation which allow mediators to serve as arbitrators, even in the same dispute. The requirements of natural justice, which are integral to the arbitration process, are largely ineffective in mediation proceedings. It is argued that, because of the ineffectiveness of the application of the rules of natural justice in mediation proceedings, the roles of mediators and arbitrators are distinct and incompatible.